Incidence, Management, and Outcome of Symptomatic Postoperative Posterior Fossa Pseudomeningocele: A Retrospective Single-Institution Experience. Issue 3 (September 2016) - Smith, Gabriel A.; Strohl, Madeline P.; Manjila, Sunil; Miller, Jonathan P.
Abstract : BACKGROUND: Pseudomeningocele is a source of considerable morbidity after posterior fossa surgery, but incidence and optimal management strategies are unclear. OBJECTIVE: To define risk factors, evaluate management strategies, and identify predictors of resolution. METHODS: A prospectively maintained database of 687 consecutive posterior fossa operations at a single institution was analyzed to identify cases of symptomatic postoperative pseudomeningocele. Retrospective analysis of treatment strategies and outcome was performed. RESULTS: Overall rate of symptomatic postoperative pseudomeningocele was 14.1% (97 cases). The highest rate was for midline posterior fossa surgery (16.5%), and the lowest rate was for retrosigmoid surgery (11.9%). Multivariate logistic regression analysis revealed that the presence of increased ventricle size on postoperative imaging predicted significantly higher risk of failure of lumbar drainage (odds ratio, 6.57; 95% confidence interval [CI], 1.18-36.59; P < .05). Cox proportional hazards analysis revealed that time to clinical resolution was significantly associated only with use of temporary lumbar drainage (hazards ratio, 2.28; 95% CI, 1.04-5.00; P < .05), and time to radiographic resolution was associated only with placement of a ventricular shunt (hazards ratio, 2.84; 95% CI, 1.19-6.78; P < .05). CONCLUSION: Pseudomeningocele is a common complication after posterior fossa surgery, but incidence is not related to age or medical comorbidity. Postoperative ventriculomegaly portends failure of temporary cerebrospinal fluid diversion, and early consideration of shunting might be appropriate in such cases. In the absence of ventriculomegaly, temporary use of a lumbar drain leads to earlier clinical resolution, but complete radiographic resolution is rare when a permanent shunt is not implanted. Further research should be performed to establish the most effective treatment strategy. ABBREVIATION: CSF, cerebrospinal fluid